Behaviour of the double concave Friction Pendulum bearing. - Fenz, Daniel M.
The double concave Friction Pendulum (DCFP) bearing is an adaptation of the well-known single concave Friction Pendulum bearing. The principal benefit of the DCFP bearing is its capacity to accommodate substantially larger displacements compared to a traditional FP bearing of identical plan dimensions. Moreover, there is the capability to use sliding surfaces with varying radii of curvature and coefficients of friction, offering the designer greater flexibility to optimize performance. This paper describes the principles of operation of the bearing and presents the development of the force?displacement relationship based on considerations of equilibrium. The theoretical force?displacement relationship is then verified through characterization testing of bearings with sliding surfaces having the same and then different radii of curvature and coefficients of friction. Lastly, some practical considerations for analysis and design of DCFP bearings are presented.
Keywords: Double concave Friction Pendulum bearing; Seismic isolation